2020
DOI: 10.1186/s41938-020-00335-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mycosis of Metarhizium (Nomuraea) rileyi on Spodoptera frugiperda infesting maize in Andhra Pradesh, India

Abstract: Background Mycosis on the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), infecting maize was observed in research farm of Regional Agricultural Research Station, Anakapalli from October 2019 to February 2020. Main body High relative humidity (94.87%), low temperature (24.11 °C), and high rainfall (376.1 mm) received during the month of September 2019 predisposed the larval instars for fungal infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Then, it gradually changed to olive blue, and sporulation began from the 12th day. This is similar to the results of Visalakshi et al (2020), who showed sporulation at 10 days and onwards.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Then, it gradually changed to olive blue, and sporulation began from the 12th day. This is similar to the results of Visalakshi et al (2020), who showed sporulation at 10 days and onwards.…”
Section: Discussionsupporting
confidence: 92%
“…Entomopathogenic fungi (EPF) are effective biocontrol agents that can provide an alternative for the integrated pest management of FAW. EPF pathogenicity is significantly affected by various environmental conditions, such as humidity, rainfall, and temperature, in a species‐specific manner (Maurya et al, 2013; Visalakshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike most synthetic insecticides, biological control agents are often host speci c and hence tend to have less effect on non-target species and the broader environment (Dodd 1959 (Dodd 1959), and entomopathogenic fungus (Beauveria bassiana) to control coffee berry borer (Hypothenemus hampei) in Colombia (Aristizábal et al 2016) and many more (van Lenteren et al 2018). In India and Uganda, various species of parasitic wasps and nematodes, predatory insects, and fungi have been implicated as playing important roles in suppressing S. frugiperda populations (Firake and Behere 2020; Visalakshi et al 2020;Otim et al 2021), highlighting the potential value of biological control, particularly within broader IPM systems.…”
Section: Introductionmentioning
confidence: 99%